From Resist to Exist: The Existence of a Woman in Novel Layangan Putus - Husda, Azizah; Nasution, Ikhwanuddin; Nasution, Siti Norma; Kembaren, Mardiah Mawar (CV Raskha Media Group, 2025)
This research is on literary criticsm which discusses on women’s existences in fighting against gender inequality. The source of data is taken from novel entitled Layangan Putus whose the main character as the woman, called Kinan. Techniques of collecting data uses literature review and library research. While the data analysis uses the interactice models by data condensation, display, and conclusion. Findings showed that there are three existences of the woman to fight the gender inequality, namely being a worker to prosper herself, being a well-educated woman to solve the problems with her ex-husband, to control her feelings while raising her children, and being a social transformer to keep her head facing on the past life, giving lessons to learn by women who fight against gender inequality such as stereotype, subordination, domestic violence, and double burden. To conclude, women should also prioritize themselves eventhough they get married and never limit their existences to live and to decide their own life.